Altering Perspectives and Preserving Diversities: A Look into Kerala’s Tribal Reform - Meena J. Panikker (Third 21st CAF Conference at Harvard, in Boston, USA. September, 2015)
India is home to the collective consciousness of 461 indigenous tribes, each with its own established set of attitudes and customs of leading life that is now not recognized as the popular culture. As such the societal development and planning by way of the modern democratic machinery hardly satisfies their requirements of the decent life they have been culturing. The mass education contradicts such requirements, and hence the planning of all procedures of rehabilitating and upgrading the indigenous population is as unsuccessful as ever. This paper tries to check why the Kerala government’s tribal reform measures failed miserably in Attappady leading to many infant deaths primarily diagnosed to have been causThird 21st CAF Conference at Harvard, in Boston, USA. September 2015, Vol. 6, Nr. 1ed by malnourishment. The main reason is that all succeeding governments were largely failures in foreseeing and implementing altering perspectives in education of these tribes whereby the diversities in their culture, living and livelihood are preserved and integrated into the education system. The budget allocations of the past few years make it very clear that the majority of the funds used was to promote education for these tribes thus striving for their progress and development. This paper also attempts to trace the marginalization of the indigenous tribes in Kerala, both at the central level and the state level, and discusses how the present governmental policies of tribal rehabilitation have altered the concept of education among them, perhaps to the extent of perpetual damage to their cultural ecology and identity politics. However the fact remains that the education system implemented was largely based on western model of education causing irreparable damage to their culture, livelihood at the cost of many lives. The same case can be universally accepted as a reference point for further evaluation and diagnosis of problems in understanding diverse perspectives of the indigenous masses. Also, the paper explores the stereotypical ways of social ethics and sense of responsibility of a nation towards the education of the indigenous tribes suggesting some remedial measures for the same which involves the urgency to reach at a consensus between their primitive practices of ecological sustenance and modern day education. It is certain that instead of taking the efforts to integrate the tribes into the mainstream cultural fabric, we need to respect their cultural perspectives and try to include their findings and research proven by the test of time into the mainstream education and research, especially those related with the study of soil, native healing and cultivation.